Conformal Antenna Design for Smart Swimming Goggles Surface. Issue 1 (1st December 2022) - Wu, Qiheng; Chen, Wencong; Li, Xingyan; Xin, Dawei; Wang, Shuai; Zhai, Baojin
Abstract: Based on the irregular undevelopable surface of the smart swimming goggles, an electric dipole conformal antenna array is proposed in this article. Through the simulation of the conformal antenna, the beam scanning area of the conformal antenna array is studied to achieve a wider radiation range. In addition, the signal strength loss of the conformal antenna in the underwater environment is discussed, and the monitoring method based on the signal strength is proposed, which is helpful for the positioning monitoring of the swimming goggles to achieve risk prevention and control of children drowning.